375 Evaluation of extruded soybean hulls for relative metabolizable energy values and as a source of fiber in monogastric nutrition. (7th December 2018) - von Schaumburg, P; Detweiler, K; Davenport, G; Utterback, P; Parsons, C; de Godoy, M
Abstract: The aims of this experiment were to determine the energy value of raw soybean hulls, in comparison to the energy values of soybean hulls post-extrusion. The roosters were precision-fed up 25 g of either raw or extruded soy hulls, then placed into individual cages with a collection tray underneath to catch excreta. After 48 h, the excreta was collected and analyzed for N, gross energy, dry matter and organic matter. The results of the rooster assay did not differ (P > 0.05) between the raw and extruded soybeans. However, the TMEn (kcal/g) were numerically smaller for the conventional roosters compared to the cecectomized. This indicates that there was very little fermentation of the soybean hulls in the ceca of the roosters. In addition to the rooster assay, a chick growth assay was conducted using Ross 308 male broiler chicks. The study lasted 14 d. Seven-day old chicks (BW: 87.0 ± SEM g). The experimental diets consisted of 7.5% and 15% inclusion of both raw and extruded soybean hulls, respectfully, added at the expense of cellulose. The chicks' BW, feed intake, and G:F ratio were all calculated throughout the study. The results of the chick assay were more striking than that of the rooster assay. Chicks fed the 15% extruded soybean hulls diet had similar performance (P > 0.05) to the positive control; a traditional soybean meal and corn diet. In conclusion, the chick growth assay, used in combination with the precision-fed rooster assay, were able to detect differences between raw and extruded soybean hulls. These data may allow different monogastric animal production systems to include soybean hulls into diet formulation. Whether it be inclusion into weight control diets, low-energy molting diets, or for low-energy, low-cost fiber products.